Management of patients with cochlear implants and ventriculoperitoneal shunts. (July 2014) - Chadwick, Keith A; Moore, Jaime; Tye, Gary W; Coelho, Daniel H
Abstract : Objectives: The aim of this study is to provide an overview of each device, discuss conditions that may predispose to the requirement of both devices, and consider pre- and post-operative issues arising from the co-existence of advanced technologies. In addition, relevant surgical anatomy and technique in the placement of both cochlear implant (CI) after ventriculoperitoneal shunt (VPS) and VPS after CI are reviewed. Methods: Review of literature. Results: Issues relevant to CI and VPS include predisposing conditions, magnetic resonance imaging compatibility, infectious risk, surgical technique, complication management, and a host of other issues. Discussion: Patients with hydrocephalus and severe-to-profound hearing loss are a unique patient population with unique pre-, intra-, and post-operative issues. Thorough understanding of the indications, radiology, anatomy, technology, and potential complications can allow for these patients to achieve the full benefit of these lifechanging surgeries.